Sensors and instrumentation. Proceedings of the 34th IMAC, a conference and exposition on structural dynamics 2016 /: Proceedings of the 34th IMAC, a conference and exposition on structural dynamics 2016. Volume 5 : (2016) - Unknown
No abstract available